Reduced B cell frequencies in cord blood of HIV-exposed uninfected infants: an immunological and transcriptomic analysis - Jin, Ye; Zhao, Jun; Qi, Tangkai; Tian, Di; Liao, Yixin; Yang, Qing; Li, Minming; Zhu, Qingqing; Chen, Jun; Shen, Yinzhong; Liu, Yabin; Lu, Hongzhou (Frontiers in Immunology, 2024)
In the course of immune development, HIV-exposed uninfected (HEU) infants exhibit abnormal immune function and increased infectious morbidity compared to HIV-unexposed uninfected (HUU) infants. Yet the specific functional phenotypes and regulatory mechanisms associated with in-utero HIV and/or ART exposure remain largely obscure. Herein, we utilized flow cytometry and RNA-seq technologies to conduct the immunological and transcriptomic profiling in cord blood from 9 HEU mother-infant pairs and 24 HUU pairs. On top of that, we compared the cord blood dataset with the maternal venous blood dataset to characterize unique effects induced by in-utero HIV and/or ART exposure. Flow cytometry immunophenotyping revealed that the level of B lymphocyte subsets was significantly decreased in HEU cord blood as compared to HUU (P < 0.001). Expression profilingbased cell abundance assessment, includes CIBERSORT and ssGSEA algorithm, showed a significantly reduced abundance of naive B cells in HEU cord blood (both P < 0.05), supporting the altered composition of B lymphocyte subsets in HEU. Functional enrichment analysis demonstrated suppressed innate immune responses and impaired immune regulatory function of B cells in HEU cord blood. Furthermore, through differential expression analysis, co-expression network analysis using WGCNA, and feature selection analysis using LASSO, we identified a 4-gene signature associated with HEU status. This signature effectively assesses B cell levels in cord blood, enabling discrimination between HEU and HUU infants. Our study provides the first comprehensive immunological and transcriptomic characterization of HEU cord blood. Additionally, we establish a 4-gene-based classifier that holds potential for predict immunological abnormalities in HEU infants.